PENGENALAN BANTUAN HIDUP DASAR (BHD) PADA MASYARAKAT TJ. PENGAPIT KOTA BATAM TAHUN 2025 - Ditte Ayu Suntara; Afif D Alba, Dedi Fatrida, Nadya Ulfa Kesumawardani, Trisya Yona Febrina, Dedy Siska, T. Eltrikanawa (JOURNAL OF COMMUNITY DEDICATION, 2025)
Basic life support (BLS) is an action taken to increase the chan survival for cardiac arrest victims. The general public can per BLS with basic information and knowledge, because the succe BLS actions is influenced by knowledge and attitudes about Basic life support (BLS) is an action taken to increase the chan survival for cardiac arrest victims. The success of BLS actio influenced by knowledge and attitudes about BLS. This Comm Service Activity was carried out in Tanjung Pengapit, Batam in May 2025, the target of this Community Service activity w residents in Tanjung Pengapit, Batam City. The results obt were the level of knowledge of residents in the lecture and simul education group before being given BLS education, namely that were in the sufficient category as many as 19 respondents (6 While a small part was in the good category as many a respondents (37%). After being given BLS education and simula data was obtained on the level of student knowledge, most of were in the sufficient category, 26 respondents (87%). Meanwh small part was in the poor category, 4 respondents (13%).